ON INTUITIONISTIC FUZZY BI-IDEALS IN GAMMA NEAR RINGS - EZHILMARAN D; DHANDAPANI A (Innovare Journal of Engineering and Technology, 2017)
In this paper, we introduce the intuitionistic fuzzy bi ideals in G-near-rings and investigate some of their related properties.